Trajectory of AKI and hospital mortality among patients with COVID-19 - Seong Geun Kim; Chung Hee Han; Sung Bong Yu; Hyeseung Lee; Soie Kwon; Yerim Kim; Jeonghwan Lee; Dong Ki Kim; Yun Kyu Oh; Chun Soo Lim; Yon Su Kim; Byung Gun Kim; et al. (Renal Failure, 2023)
Background Acute kidney injury (AKI) in COVID-19 patients is associated with poor prognosis. Characterization of AKI by timing and trajectory and early prediction of AKI progression is required for better preventive management and the prediction of patient outcomes.Methods A total of 858 patients who were hospitalized due to coronavirus disease 2019 (COVID-19) were retrospectively enrolled from December 2020 to August 2021. The occurrence of AKI was evaluated throughout hospitalization. The hazard ratios (HRs) of mortality outcomes according to the trajectory of AKI were measured using Cox regression models after adjustment for multiple variables.Results Among 858 patients, 226 (26.3%) presented AKI at admission, and 44 (5.1%) developed AKI during hospitalization. Patients with AKI at admission or hospital-acquired AKI had a higher risk of mortality than those without AKI, with HRs of 9.87 (2.81–34.67) and 13.74 (3.57–52.84), respectively. Of 226 patients with AKI at admission, 104 (46.0%) recovered within 48 hr, 83 (36.7%) had AKI beyond 48 hr and recovered in 7 days, and 39 (17.3%) showed no recovery from AKI on Day 7. Delayed recovery and persistent AKI were significantly associated with an increased risk of mortality, with HRs of 4.39 (1.06–18.24) and 24.33 (7.10–83.36), respectively.Conclusions The onset and progression of AKI was significantly associated with in-hospital mortality in patients with COVID-19. A thorough observation of the recovery trajectory of early AKI after infection is necessary.